N-Heterocyclic carbene catalyzed esterification of aromatic aldehydes with alcohols under aerobic conditions - Kiran, I. N. Chaithanya; Lalwani, Komal G.; Sudalai, Arumugam (RSC Advances, 2013)
A simple, organocatalytic procedure for the direct oxidative esterification of a variety of aromatic aldehydes with alcohols has been described that affords the corresponding aromatic esters in high yields. The method employs N-heterocyclic carbenes as catalysts and molecular O-2 as an oxidant under ambient conditions.

First enantioselective synthesis of surinamensinol B and a non-natural polysphorin analogue by a two-stereocentered hydrolytic kinetic resolution - Lalwani, Komal G.; Sudalai, Arumugam (European Journal of Organic Chemistry, 2015)
An efficient and economical approach to the synthesis of antitumor and anti-inflammatory surinamensinol B (1) and antimalarial polysphorin analogue 2 has been achieved with high enantiomeric purity (96% ee) by starting from commercially available 3,4,5-trimethoxybenzaldehyde. The key steps of the strategy include a Co-catalyzed two-stereocentered hydrolytic kinetic resolution (HKR) of racemic 2[( methoxymethoxy)(3,4,5-trimethoxyphenyl)methyl] oxirane (13) as the chiral inducing step followed by a Mitsunobu reaction. Chiral epoxide 14 and chiral diol 15 were utilized in the syntheses of both compounds.
Keywords: Biological activity; Enantioselectivity; Kinetic resolution; Natural products; Total synthesis

Organocatalytic [4+1]-annulation approach for the synthesis of densely functionalized pyrazolidine carboxylates - Lalwani, Komal G.; Aher, Ravindra D.; Sudalai, Arumugam (RSC Advances, 2015)
A novel one-pot [4+1]-annulation process for the asymmetric synthesis of densely functionalized pyrazolidine carboxylates is described. The in situ generated gamma-hydrazino-alpha,beta-unsaturated ester obtained via proline catalysis acts as a four-atom component, and Corey's sulfur ylide or ethyl bromoacetate acts as a one-atom carbon source to construct pyrazolidine carboxylate units in a highly enantio- and diastereoselective fashion.

Short enantioselective synthesis of ephedrine, amphetamine and their analogues via two stereocentered Co(III)-catalyzed hydrolytic kinetic resolution of racemic syn-benzyloxy epoxide - Lalwani, Komal G.; Sudalai, Arumugam (Tetrahedron Letters, 2015)
An efficient route for the synthesis of 6 drugs belonging to phenethylamine and amphetamine classes in excellent overall yields and high optical purity has been described. The strategy involves introduction of stereogenic centers by means of two-stereocentered Co(III)-catalyzed hydrolytic kinetic resolution (HKR) of racemic syn-benzyloxy epoxide followed by Pd-catalyzed regioselective cationic hydrogenation of amino alcohols as the key reactions. (C) 2015 Elsevier Ltd. All rights reserved.
Keywords: Amphetamine; Cationic hydrogenation; Hydrolytic kinetic resolution; Phenethylamine; Stereogenic centers

Concise enantioselective synthesis of (+)-L-733,060 and (+)-T-2328 via sequential proline catalysis - Lalwani, Komal G.; Sudalai, Arumugam (Synlett, 2016)
A new, sequential proline-catalyzed approach to the synthesis of (+)-L-733,060 and (+)-T-2328 in high optical purity (93% ee) is described starting from phenyl N-Boc imine. The strategy involves proline-catalyzed Mannich reaction of an arylimine with acetaldehyde followed by -aminoxylation/Wittig olefination in a sequential fashion as the key steps.
Keywords: Aminoxylation; imine; Mannich reaction; olefination; sequential

Organocatalytic route to enantioselective synthesis of ceramide trafficking inhibitor HPA-12 - Lalwani, Komal G.; Sudalai, Arumugam (Tetrahedron Letters, 2016)
A new organocatalytic approach to the synthesis of ceramide trafficking inhibitor HPA-12 has been described starting from phenacyl bromide. The strategy involves chiral CBS reduction of gamma-ketoester and proline-catalyzed alpha-amination reaction of aldehyde followed by reduction as the key chirality inducing steps. (C) 2016 Elsevier Ltd. All rights reserved.
Keywords: alpha-Amination; CBS reduction; Ceramide; Organocatalytic; Proline